Organizational, individual, and psychosocial determinants of burnout syndrome among hospital nurses: A scoping review - Rahayu, Rahayu; Haryanto, Haryanto; Suriadi, Suriadi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Burnout among nurses is a Connon occupational health problem in hospital settings and has important for the quality of nursing care. Burnout develops as a response for prolonged work-related stress, particularly among nurses working in environments with high workload and emotional demands. Evidence indicates that nurse burnout is influenced by organizational, individual and psychosocial factors. Purpose: To map and examine organizational, individual and psychosocial determinants influencing burnout among hospitals nurses. Method: A scoping review was conducted in accordance with the PRISMA-ScR guidelines. National and international studies addressing burnout among hospital nurses were identified. Quantitative, qualitative and mixed-methods studies were included. Data were extracted and synthesized using narrative and thematic approaches. Results: A total of 20 articles met the inclusion criteria for this study. The synthesis identified three of determinants influencing burnout among hospital nurses: organizational determinants (workload, working hours, shift system, managerial support and role clarity), individual determinants (age, years experience, resilience, locus of control and work motivation), and psychosocial determinants (social support, interpersonal relationships, work climate and career development opportunities). Organizational determinants were the most consistently reported across studies. Conclusion: Burnout among hospital nurses is a multidimensional phenomenon shaped by the interaction of organizational, individual and psychosocial factors. Preventive efforts should prioritize organizational improvements, alongside strengthening individual capacities and supportive environments. Keywords: Burnout; Determinants; Hospitals; Nurses; Scoping Review.